The Dependence of Cold and Hot Patches on Local Plasma Transport and Particle Precipitation in Northern Hemisphere Winter - Duan Zhang; Qing‐He Zhang; Y.‐Z. Ma; Kjellmar Oksavik; L. R. Lyons; Zan‐Yang Xing; Marc Hairston; Z.‐X. Deng; J.‐J. Liu (Geophysical Research Letters)
Abstract By using a database of 4,634 cold patches (high density and low electron temperature) and 4,700 hot patches (high density and high electron temperature) from Defense Meteorological Satellite Program F16 in 2005–2018 winter months (October–March), we present a statistical survey of the distributions of polar cap patches for different interplanetary magnetic field (IMF) orientations and ionospheric convection geometries. We investigate the dependence of cold and hot patches on local plasma transport and soft‐electron precipitation. Our results indicate that: in winter, (a) more cold and hot patches occur in the stronger anti‐sunward flow organized by different IMF orientations. (b) cold patches are frequent near the central polar cap, while hot patches are closer to the auroral oval. (c) enhanced anti‐sunward flow (E × B drift) mainly contributes to cold patch occurrence under Bz < 0, and soft‐electron precipitation contributes to hot patch occurrence both under southward and northward IMF.